2013
DOI: 10.3402/dfa.v4i0.21361
|View full text |Cite
|
Sign up to set email alerts
|

Charcot foot and ankle with osteomyelitis

Abstract: This paper presents a review of the current literature discussing topics of Charcot osteoarthropathy, osteomyelitis, diagnosing osteomyelitis, antibiotic management of osteomyelitis, and treatment strategies for management of Charcot osteoarthropathy with concurrent osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 54 publications
0
33
0
2
Order By: Relevance
“…Severe foot infection and concurrent CN carries a morbidity and mortality that can be as high as 35%, even when infection is managed appropriately. 5 Milne et al 6 cite a missed diagnosis of acute CN in 79% of cases with a delay in the correct diagnosis of up to 29 weeks; this delay is attributed to the rarity of the condition and lack of clinician education. Pakarinen et al 9 undertook a small study of patients living with chronic CN and found a statistically significant difference in functional outcome and walking distance when study patients were correctly diagnosed with the condition within 3 months of symptom onset versus those receiving a later diagnosis.…”
Section: Diagnostic Cluesmentioning
confidence: 97%
See 4 more Smart Citations
“…Severe foot infection and concurrent CN carries a morbidity and mortality that can be as high as 35%, even when infection is managed appropriately. 5 Milne et al 6 cite a missed diagnosis of acute CN in 79% of cases with a delay in the correct diagnosis of up to 29 weeks; this delay is attributed to the rarity of the condition and lack of clinician education. Pakarinen et al 9 undertook a small study of patients living with chronic CN and found a statistically significant difference in functional outcome and walking distance when study patients were correctly diagnosed with the condition within 3 months of symptom onset versus those receiving a later diagnosis.…”
Section: Diagnostic Cluesmentioning
confidence: 97%
“…2,3,6,7 The condition is usually unilateral but the contralateral foot may be affected in up to 25%-30% of patients. 5,6,8 If pain is present in the affected foot it is usually mild or absent altogether, and on occasion, the patient may recall a preceding trauma to the foot. 2,5,6 An infrared dermal thermometer can be used to detect a >2.0 C temperature difference between the affected foot region in acute CN and the contralateral, unaffected foot in the same region.…”
Section: Diagnostic Cluesmentioning
confidence: 98%
See 3 more Smart Citations